Analysing The Effects of a Brand Scandal: Carasun's Buzz Marketing on Brand Attitude and Purchase Intention - Lina, Hasna Nur (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2024)
Buzz marketing, a fabricated type of word-of-mouth was used by Carasun, an Indonesian sunscreen brand, in February 2022. The brand received a backlash after Indonesian netizens found them using buzz marketing to turn down an upcoming sunscreen product from another brand, Skin Game. As the unethical tactic became viral on Twitter and Instagram, many of Carasun’s consumers and social media users criticised it, and some also said to blacklist the brand. Past studies showed brand scandals can have negative effects on consumers’ expectations, reputation, sales, brand equity, buying motivations, and marketing effectiveness. Research on the impact of the brand scandal on consumers was conducted using the survey method to determine their attitude and purchase intention towards Carasun post-scandal. Respondents were 106 Indonesian skincare users aged 15 to 34 who were aware of the Carasun issue. This research revealed the scandal does not impact both consumers' attitudes and purchase intentions. Most respondents were aware of the scandal (95.3%) and agreed that the scandal is a serious issue (81.1%). However, their attitudes, specifically, their beliefs and feelings about Carasun, remained positive. There was a possibility that respondents rejected the unfavourable brand news and preferred to remain purchasing the brands because of the usefulness and benefit that can be obtained from these brands.